Exploring the perceptions of first-generation college students with strengths-based development experiences - Lerer, Steven I., author; Kuk, Linda, advisor; Gonzalez-Voller, Jessica, committee member; Gupta, Kalpana, committee member; Tungate, Susan, committee member (Colorado State University. Libraries, 2021)
The purpose of this qualitative research study was to explore perceptions of first-generation college students with strengths-based development experiences. Strengths-based development experiences were defined as those that leveraged a student's results from the CliftonStrengths® assessment provided by the Gallup Organization. This study used a phenomenological approach designed to illuminate the shared experience the participants had when engaging in strengths-based development. Seven first-generation college students from three 4-year public colleges participated in this interview-based study. Results showed that each student embarked on a strengths-based development journey unique to them, but all experienced a similar phenomenon. These first-generation college students experienced personal self-discovery and validation of what makes them unique through strengths-based development. Participants' journeys were expanded and confirmed by individuals and communities also on their own personal strengths-based journeys. These experiences and relationships ultimately led participants to an active and conscious application of talent in all aspects of their collegiate life. Intersection with others involved in strengths-based development, whether students, staff, faculty, or community members, was a critical component in the phenomenon. Without such experiences, the phenomenon would have been unlikely to occur. Description of the phenomenon was supported by five superordinate themes with two subordinate themes for each. These superordinate themes were (a) It's Just Natural for Me containing the subordinate themes of Like a Bear Hug and Understanding Increases Over Time, (b) With Whom I Spend My Time containing the subordinate themes of This Is Who I Am and Finding the Right Partners, (c) Leveraging My Strengths containing the subordinate themes of Confidence to Step Up and Recommended to Apply, (d) Helped Me Along My Path containing the subordinate themes of Confirm or Adjust and Supported by Coaching, and (e) Finding Community Through Strengths containing the subordinate themes of Campus Communities and Beyond the Campus Boundaries. This research is the first study to explore strengths-based development experiences through the lens of first-generation college students. It extends existing research into a unique and important population of students on college campuses. This research provides meaningful suggestions for practice by higher education administrators when utilizing the CliftonStrengths® assessment with first-generation college students. This research provides suggestions for higher education administrators considering bringing CliftonStrengths to their campus. Topics for future research are also included to expand the scope of the use of CliftonStrengths on college campuses.
Keywords: college students; positive psychology; strengths-based development; first-generation college students; CliftonStrengths; strengths